Textual, Linguistic, and Historical Examination of Rare Manuscripts - Lutfullayeva, Durdona; Jabbarov, Ulugbek; Rashidova, Ma’mura; Saidov, Javohir; Kan, Viktoriya; Matkarimov, Nizomjon; Matkarimov, Inomjon (Indian Journal of Information Sources and Services, 2025)
The paper offers a wide-ranging survey of offbeat manuscripts using textual, linguistic, and historical approaches with focus on the active interplay between conventional philological analysis and modern digital methods. By way of examination of the multifaceted nature of manuscript studies—from codicology and textual criticism to machine learning and digital paleography—the research highlights how writing in the past remains a rich source of information regarding cultural, religious, and linguistic advancement in and across areas and centuries. Based on varied examples such as Central Asian Arabic epigraphy, fragments of Judeo-Arabic incantations, and early Christian Greek manuscripts, the article demonstrates how textual reconstruction, linguistic diversity, and material analysis enhance manuscript heritage in a more comprehensive way. The article also considers the impact of environmental and preservation factors on legibility of manuscripts, and the technical and ethical implications of digitisation. By way of interdisciplinary case studies and cutting-edge technologies like hyperspectral imaging and AI-based analysis, the book sets the importance of rare manuscripts as embodied vessels of human knowledge. In the end, the article encourages an integrated approach that unites conventional historical scholarship and computational techniques to maximize the preservation, accessibility, and scholarly understanding of rare and fragile textual gems.